2015
DOI: 10.1089/biores.2015.0008
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Gases and Ice Fracturing During the Freezing of a Multicellular Organism: Lessons from Tardigrades

Abstract: Three issues are critical for successful cryopreservation of multicellular material: gases dissolved in liquid, thermal conductivity of the tissue, and localization of microstructures. Here we show that heat distribution is controlled by the gas amount dissolved in liquids and that when changing the liquid into solid, the dissolved gases either form bubbles due to the absence of space in the lattice of solids and/or are migrated toward the concentrated salt and sugar solution at the cost of amount of heat requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…The type of gas bubble formation was described in Ref. (34). The remaining hyperconcentrated solution was in the space between the growing ice crystals.…”
Section: Resultsmentioning
confidence: 99%
“…The type of gas bubble formation was described in Ref. (34). The remaining hyperconcentrated solution was in the space between the growing ice crystals.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, it is known that water typically traps dissolved air [ 32 , 33 ]. The dissolved air is presumed to be dischargeable from ice [ 33 , 34 ] during ice solidification as a result of the absence of space in ice lattices [ 34 ]. This principle is occasionally noted to prepare clear ice in the industry.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic tissue "bleaching" is partly attributed to a transient blood vessels constriction and the subsequent reduction of the local blood content [3] and partly to the ice crystal and micro-babbles in the tissues. Work by Kletetschka et al [17] showed that depending on the cell structures, which act as nucleation centers, the super-cooled inter-cellular fluids freeze instantaneously forming small crystalline structures. Furthermore, under these conditions of rapid freezing, dissolved gasses inside the cell cannot escape from solution, becoming trapped in the ice forming microscopic bubbles [18,19].…”
Section: Background Of Measurement Techniquementioning
confidence: 99%